Da conformidade à segurança : reagregando sistemas sociotécnicos complexos na indústria de óleo e gás - Fogaça, Lucas Bertelli (2021)
Many complex sociotechnical systems have Safety management as something interwoven with their main activity. Some examples include safety critical industries and high loss of life potential such as aviation, nuclear power, health and oil and gas. Literature on these systems have been discussing the stagnation of Safety levels in these industries, despite an increase in technological and regulation. The main objective of this thesis was to question the effectiveness of safety management systems in mature complex sociotechnical systems. These systems, common throughout these industries, show a tendency to evolve to self-reference seeking safety on regulatory compliance and over relying in written procedures. This research presents a panorama of the many movements and influences that happened in the safety science since the first industrial revolution and makes use of the Actor-network Theory as a theoretical and methodological approach seeking to reconcile the predominantly technical solutions in these fields and the sociomaterial associations that are usually left as something to be controlled or even, the source of problems in these systems. This thesis was explored the Oil and gas industry, which offers a unique context of maturity, plurality in management tools and approaches alongside technological heterogeneity. Among the main contributions, we defend that the safety management processes of mature sociotechnical systems induce bureaucratization and overreliance on written norms and overregulation, creating systems where compliance create important gaps in safety. This is further increased by the historical employment of functionalist and positivist ontologies that segregate the technical and the social, creating compliant systems that are unable to cope with complexity and thus, become unsafe.